Long-term AIDS-related PCNSL outcomes with HD-MTX and combined antiretroviral therapy. (22nd August 2017) - Moulignier, Antoine; Lamirel, Cédric; Picard, Hervé; Lebrette, Marie-Gisèle; Amiel, Corinne; Hamidi, Mohammed; Polivka, Marc; Mikol, Jacqueline; Cochereau, Isabelle; Pialoux, Gilles
Abstract : Objective: To assess the characteristics and outcomes of patients with AIDS-related primary CNS lymphoma (AR-PCNSL) in the combined antiretroviral therapy (cART) era systematically treated with high-dose methotrexate (HD-MTX). Methods: We retrospectively analyzed (intention-to-treat analysis) 51 consecutive patients with AR-PCNSL (median age 39 years) who were diagnosed from 1996 to 2014 and treated with a median of 6 (range 1–15) infusions of HD-MTX (3 g/m 2 ) combined with cART. Results: Median all-patients' and survivors' follow-up lasted 23 (range 0–186) and 76 (range 23–186) months, respectively. At PCNSL diagnosis, 83% of the patients were on cART, median plasma HIV load was 175, 600 copies/mL, and median CD4+ T-cell count was 24/μL. Median Eastern Cooperative Oncology Group performance status was 2 (range 1–4). Median overall survival (OS) was 5.7 years, with 5- and 10-year rates of 48% and 41%. Median time to progression was not reached (69% at 10 months). PCNSL was the direct cause of 14 deaths, all observed within the 10 months after its diagnosis: 6 patients died before HD-MTX could be administered, 4 had refractory disease, and 4 relapsed. Multivariate analyses retained time interval between AIDS diagnosis and PCNSL diagnosis, age at AR-PCNSL diagnosis, and deep brain structure involvement as independent OS-predictive factors. To restore effective immune function, cART tailored to HIV genotypes was started and combined with HD-MTX; no interactions and no immune reconstitution inflammatory syndrome occurred. No patient died of acute treatment-related toxicity, and 21 of 51 (41%) patients experienced grade 3/4 toxicity. Conclusions: Combined short-term HD-MTX monochemotherapy and optimal cART simply and effectively treat AR-PCNSL, achieving long-term survival with few relapses. Classification of evidence: This study provides Class IV evidence that short-term HD-MTX monochemotherapy improves long-term survival of patients with AIDS with primary CNS lymphoma receiving cARTs.